MODERN ALGORITHMS OF POSTURAL DISTURBANCES IN CLINICAL PRACTICE - V. I. Dotsenko; V. I. Usachev; S. V. Morozova; M. A. Skedina (Медицинский совет, 2017)
Hold upright, vertical body position and bipodal locomotion-the key components of a functional system of Antigravity. Get objective data about the postural regulation was made possible thanks to the introduction into clinical practice statokinezimetrii (all)-method of qualitative and quantitative analysis of oscillatory process of Center of pressure stop on a plane of leg vertically-installed or that you are using less of a seated person. Qualitatively changed the accuracy of diagnosis of stabilometric vector analysis, using which a doctor can assess  the effectiveness  of treatment, as well as the stages  of examination and treatment to conduct statistical assessment of the credibility of the differences of variability of dynamic stabilization Factor indicator  (FDC) of the patient.